ANALISIS PERFORMA COOLING TOWER JENIS INDUCED DRAFT COUNTER FLOW DI POWER PLANT PT. X - Purba, Jhon Hericson; Syaputri, Alfina (Politeknik Negeri Batam, 2025)
The cooling tower is a crucial component in the water cooling system of a power plant. During its operation, the cooling process occurs when the water entering the cooling tower undergoes heat transfer through direct contact with cool air, resulting in evaporation. This process leads to water losses in the form of evaporation loss and blowdown, which affect the cooling capacity of production equipment. This study aims to analyze the performance of an induced draft counter-flow cooling tower at PT. X by examining parameters such as range, approach, cooling effectiveness, evaporation loss, and cooling capacity. The results indicate that the cooling tower operates with a range of 6.03°C, an approach of 4.4°C, a cooling effectiveness of 58.75%, a make-up water rate of 43.07 m³/h, and a cooling capacity of 29,419.58 kW. A strong correlation (0.958) between inlet and outlet water temperatures demonstrates consistent heat transfer performance. The system shows improved performance, with ΔT increasing from 2.78°C in 2015 to 6.44°C in 2024. Based on the analysis, it can be concluded that the cooling tower remains feasible for operation but requires regular maintenance to optimize performance.